Using Income Tax Incentives Article 21 Borne by the Government on Companies Impacted by Covid-19 - Atin Hafidiah; Dusa Sumartaya; Yana Maulana (Indonesian Journal of Multidisciplinary Science, 2021)
This research is about the use of incentives provided by the government during the Covid-19 pandemic to companies that are included in the Classification of Business Fields to get relief from PPh article 21 borne by the government (DTP). The purpose of this study is to find out whether PT HSK is included in the Classification of Business Fields as stipulated and how to calculate PPh article 21 during the pandemic period, as well as reporting. From the results of the study, it can be concluded that the company is one that is included in the Classification of Business Fields and is entitled to the Income Tax Article 21DTP tax incentive, besides that it can also be concluded that the company has carried out calculations, reporting SPT Period PPh Article 21 and Realization Reports during the Covid-19 pandemic in accordance with Minister of Finance Regulation Number 23 of 2020 for the period April to June 2020 and Minister of Finance Regulation Number 86 of 2020 for the period until December 2020.